2008
DOI: 10.1111/j.1460-9568.2007.06016.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of early oestrogens in the central processing of sexually relevant olfactory cues in female mice

Abstract: We previously found that female aromatase knockout (ArKO) mice showed less investigation of socially relevant odours as well as reduced sexual behaviour. We now ask whether these behavioural deficits might be due to an inadequate processing of odours in female ArKO mice. Therefore, we exposed female ArKO mice to same- and opposite-sex urinary odours and determined the expression of the immediate early gene c-Fos along the main and accessory olfactory projection pathways. We included ArKO males in the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
5
33
0
Order By: Relevance
“…The authors concluded that in mice (unlike rats) the perinatal actions of testosterone that defeminize the olfactory circuit that processes male pheromones do not depend on the estrogenic metabolites of this testicular steroid, but instead on the action of testosterone itself, acting upon neurons that express androgen receptors. This is confirmed by observations in estrogen-deficient male aromatase knockout (ArKO) mice which showed a normal, male-typical expression of Fos following exposure to male pheromones (Pierman et al, 2008).…”
Section: Sex Differences In the Detection And Processing Of Reproductsupporting
confidence: 64%
See 1 more Smart Citation
“…The authors concluded that in mice (unlike rats) the perinatal actions of testosterone that defeminize the olfactory circuit that processes male pheromones do not depend on the estrogenic metabolites of this testicular steroid, but instead on the action of testosterone itself, acting upon neurons that express androgen receptors. This is confirmed by observations in estrogen-deficient male aromatase knockout (ArKO) mice which showed a normal, male-typical expression of Fos following exposure to male pheromones (Pierman et al, 2008).…”
Section: Sex Differences In the Detection And Processing Of Reproductsupporting
confidence: 64%
“…The Fos responses to male vs. female urinary volatiles in different forebrain regions of ovariectomized female mice (Martel and Baum, 2007) resembled the sex difference in Fos responses to soiled bedding already described, above (Bodo and Rissman, 2007;Halem et al, 1999;Pierman et al, 2008). Thus, male, but not female (same-sex), urinary volatiles augmented Fos expression in the BNST and MPOA of ovariectomized female mice given no ovarian hormones, with a parallel (non-significant) trend being seen in the medial amygdala.…”
Section: Sex Differences In the Detection And Processing Of Volatile mentioning
confidence: 57%
“…However, the different capacities of WT and ArKO females to discriminate volatile urinary odors from ovariectomized females treated with estradiol as opposed to oestradiol + progesterone cannot be explained by a difference between females of these two phenotypes in the ability of these two odors to activate distinguishable clusters of MOB glomeruli [70], suggesting that the central processing of social odors may be affected in female ArKO mice. In this respect, ArKO females that were treated with estradiol benzoate in adulthood to correct for their estrogen deficiency showed a normal, female-typical, Fos activation at the level of the olfactory bulbs when exposed to male urinary odors, but Fos responses were affected at more central levels [85]. Indeed, male odors still induced significant Fos expression in the medial amygdala of ArKO females, although this increase was clearly reduced in comparison with WT female mice, and failed to activate the VMH, a brain region critical for the expression of reproductive behavior in female mice.…”
Section: Sexual Differentiation Of Both Olfactory Systemsmentioning
confidence: 99%
“…The anti-c-Fos polyclonal rabbit and goat antibody was raised against a N-terminal peptide from human c-Fos (amino acids [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This antibody recognized a 62-kDa protein on Western blotting corresponding to the expected molecular weight of c-Fos (manufacturer's technical datasheet).…”
Section: C-fosmentioning
confidence: 99%